Automating judgment? Algorithmic judgment, news knowledge, and journalistic professionalism. (May 2018) - Carlson, Matt
Journalistic judgment is both a central and fraught function of journalism. The privileging of objectivity norms and the externalization of newsworthiness in discourses about journalism leave little room for the legitimation of journalists' subjective judgment. This tension has become more apparent in the digital news era due to the growing use of algorithms in automated news distribution and production. This article argues that algorithmic judgment should be considered distinct from journalists' professional judgment. Algorithmic judgment presents a fundamental challenge to news judgment based on the twin beliefs that human subjectivity is inherently suspect and in need of replacement, while algorithms are inherently objective and in need of implementation. The supplanting of human judgment with algorithmic judgment has significant consequences for both the shape of news and its legitimating discourses.